2017
DOI: 10.1111/jcpt.12581
|View full text |Cite
|
Sign up to set email alerts
|

Does the “script” need a rewrite? Is medication advice in television medical dramas appropriate?

Abstract: Medication was often used for the correct indication in television medical dramas; however, key safety checks were frequently omitted and other medication-related advice, including dose, was less reliable and accurate. Pharmacists were rarely involved in providing medication advice. Viewers should not base medication-related decisions solely on what they see in television medical dramas, and any medication-related advice should be interpreted with extreme caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A thematic analysis comparing withdrawal of life support on Grey’s Anatomy and in a real intensive care unit also found discrepancies in how death is represented on television (Chartrand, 2020). On the other hand, a review of 424 medications given on five different medical dramas found that they were often given for the correct indication although there was a lack of proper safety checks and dosing (Cowley et al, 2017). There is also a growing consensus that these shows can offer an opportunity to discuss medical ethics, education, and professionalism (Czarny et al, 2010; Hirt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A thematic analysis comparing withdrawal of life support on Grey’s Anatomy and in a real intensive care unit also found discrepancies in how death is represented on television (Chartrand, 2020). On the other hand, a review of 424 medications given on five different medical dramas found that they were often given for the correct indication although there was a lack of proper safety checks and dosing (Cowley et al, 2017). There is also a growing consensus that these shows can offer an opportunity to discuss medical ethics, education, and professionalism (Czarny et al, 2010; Hirt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Of the medication orders, 88.1% were considered accurate, with the most common reason for inaccuracy being incorrect dose, representing 44.6% of the errors, followed by inappropriate indication (43%). Recently, our team further explored this topic . After studying a series of random episodes from the popular medical dramas House, Grey’s Anatomy, Royal Pains, Doc Martin, and Nurse Jackie (20 hours per TV show) for the appropriateness of their medication advice, some interesting statistics were revealed.…”
mentioning
confidence: 99%
“…Recently, our team further explored this topic. 8 After studying a series of random episodes from the popular medical dramas House, Grey's Anatomy, Royal Pains, Doc Martin, and Nurse Jackie(20 hours per TV show) for the appropriateness of their medication advice, some interesting statistics were revealed. Although the medication indication was correct 71% of the time for all shows combined, the adherence to evidencebased guidelines was generally poor, with an overall 37% agreement with guidelines.…”
mentioning
confidence: 99%